2018
DOI: 10.1161/circresaha.118.313429
|View full text |Cite
|
Sign up to set email alerts
|

A Miniaturized, Programmable Pacemaker for Long-Term Studies in the Mouse

Abstract: Rationale: Cardiac pacing is a critical technology for the treatment of arrhythmia and heart failure. The impact of specific pacing strategies on myocardial function is an area of intense research and high clinical significance. Mouse models have proven extremely useful for probing mechanisms of heart disease, but there is currently no reliable technology for long-term pacing in the mouse. Objective: We sought to develop a device for long-term pacing studies in mice. We evaluated the device for i) treating 3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
13
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 33 publications
(33 reference statements)
2
13
1
Order By: Relevance
“…In contrast to the experiments in rats, which demonstrated increased AF substrate following more than 2 days of RAP, we did not find any indications for increased AF substrate formation in unanesthetized mice exposed to RAP for up to 7 consecutive days at 1200 bpm. These findings seem consistent with the recently reported results of Hulsmans et al (2018). While Hulsmans et al (2018) managed to perform long-lasting LA pacing using a leadless Medtronic pacemaker adapted for mice experimentation, AF inducibility tested in the anesthetized state at the end of 28 days demonstrated only a mild tendency of increase, which did not reach statistical significance.…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations
“…In contrast to the experiments in rats, which demonstrated increased AF substrate following more than 2 days of RAP, we did not find any indications for increased AF substrate formation in unanesthetized mice exposed to RAP for up to 7 consecutive days at 1200 bpm. These findings seem consistent with the recently reported results of Hulsmans et al (2018). While Hulsmans et al (2018) managed to perform long-lasting LA pacing using a leadless Medtronic pacemaker adapted for mice experimentation, AF inducibility tested in the anesthetized state at the end of 28 days demonstrated only a mild tendency of increase, which did not reach statistical significance.…”
Section: Discussionsupporting
confidence: 89%
“…These findings seem consistent with the recently reported results of Hulsmans et al (2018). While Hulsmans et al (2018) managed to perform long-lasting LA pacing using a leadless Medtronic pacemaker adapted for mice experimentation, AF inducibility tested in the anesthetized state at the end of 28 days demonstrated only a mild tendency of increase, which did not reach statistical significance. Interestingly, Hulsmans et al (2018) also report molecular findings which are consistent with increased inflammatory response in the atrial tissue and are in line with our current microarray findings in the rats (discussed below).…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…in the unanesthetized state) has not been reported thus far to the best of our knowledge. Recently, Hulsmans et al 19 reported the development of a miniaturized pacemaker for long-term pacing studies in rodents. However, although this technically-advanced system may open remarkable new opportunities, the currently introduced pacer could not be used for the electrophysiological (EP) testing, which was done conventionally under deep anesthesia as a single terminal procedure.…”
mentioning
confidence: 99%